Doctors' personal health care choices: A cross-sectional survey in a mixed public/private setting - Chao David VK; Li Donald KT; Lam Tai; Tse Eileen YY; Chen Julie Y; Kwan Chi (BMC, 2008)
Abstract Background Among Western countries, it has been found that physicians tend to manage their own illnesses and tend not have their own independent family physicians. This is recognized as a significant issue for both physicians and, by extension, the patients under their care, resulting in initiatives seeking to address this. Physicians' personal health care practices in Asia have yet to be documented. Methods An anonymous cross-sectional postal questionnaire survey was conducted in Hong Kong, China. All 9570 medical practitioners in Hong Kong registered with the Hong Kong Medical Council in 2003 were surveyed. Chi-square tests and logistic regression models were applied. Results There were 4198 respondents to the survey; a response rate of 44%. Two-thirds of respondents took care of themselves when they were last ill, with 62% of these self-medicating with prescription medication. Physicians who were graduates of Hong Kong medical schools, those working in general practice and non-members of the Hong Kong College of Family Physicians were more likely to do so. Physician specialty was found to be the most influential reason in the choice of caregiver by those who had ever consulted another medical practitioner. Only 14% chose consultation with a FM/GP with younger physians and non-Hong Kong medical graduates having a higher likelihood of doing so. Seventy percent of all respondents believed that having their own personal physician was unnecessary. Conclusion Similar to the practice of colleagues in other countries, a large proportion of Hong Kong physicians self-manage their illnesses, take self-obtained prescription drugs and believe they do not need a personal physician. Future strategies to benefit the medical care of Hong Kong physicians will have to take these practices and beliefs into consideration.